The impact of team design on team innovations for organisational performance: the case of parallel teams in Malaysia - Abdullah, Maznah (Curtin University, 2014)
Organisational theories emphasised that team design factors do not influence team innovation directly. Therefore, with parallel-team as a research context, this research investigated how the team design influences team innovation through innovation-climates and reflexivity. The contributions of innovations by the parallel-teams to operational and organisational performances were also examined. The findings of this research are practically useful to the managers and leaders in formulating a design of their parallel-teams for a higher innovation level.